PENGARUH KREATIVITAS TERHADAP INTENSI BERWIRAUSAHA MELALUI EFIKASI DIRI SISWA SMKN 3 DEPOK - Anggita Asmarani; Widya Parimita; Christian Wiradendi Wolor (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research aims to determine the influence of creativity on entrepreneurial intention through self efficacy of student’s class XII at SMKN 3 Depok. This research method uses quantitative research methods. The sampling technique used proportionate random sampling with a total sample of 155 students. Model in this research used a path analysis model using Structural Equation Modeling Partial Least Square (SEM-PLS) version SmartPLS 3.0. Based on the analysis, it was found that creativity had a significant direct effect on entrepreneurial intention, creativity had a significant direct effect on self efficacy, self efficacy had a significant direct effect on entrepreneurial intention, and creativity had a significat indirect effect on entrepreneurial intention through self efficacy.